The potential of bacteria isolated from earthworm intestines, vermicompost and liquid vermicompost to produce indole-3-acetic acid (IAA) - Arraktham, S.; Tancho, A.; Niuamsup, P.; Rattanawaree, P. (International Journal of Agricultural Technology, 2016)
Indole-3-acetic acid (IAA) is the most important member of the auxin class, which function as inducing cell division and cell elongation for plant growth and development. There are several Plant Growth-Promoting Rhizobacteria (PGPR), that colonize the rhizosphere and plant roots can producing IAA. But some groups of beneficial bacteria in nature do not move around; instead, they build colonies in one place. Because of this, they have little ability to promote the growth of plants in nature without being added into the soil at the root of the plants. This research we found that two IAA producing bacterial strains (A-2 and AnA-10) were isolated from the intestines of endogeic earthworms M. posthuma and identified as Enterobacter spp. based on 16S rDNA sequence homology were able to produced the amount of IAA 119.83 and 131.99 µg/ml. respectively. The results of this research both strains possess great potential to be developed as bio-fertilizers which might be enhance plant growth through IAA production with the presence of M. posthuma could led to multiply and divergent dynamics of bacterial community in soils.